1998
DOI: 10.1094/mpmi.1998.11.7.643
|View full text |Cite
|
Sign up to set email alerts
|

Induced Resistance Responses in Maize

Abstract: Systemic acquired resistance (SAR) is a widely distributed plant defense system that confers broad-spectrum disease resistance and is accompanied by coordinate expression of the so-called SAR genes. This type of resistance and SAR gene expression can be mimicked with chemical inducers of resistance. Here, we report that chemical inducers of resistance are active in maize. Chemical induction increases resistance to downy mildew and activates expression of the maize PR-1 and PR-5 genes. These genes are also coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(130 citation statements)
references
References 73 publications
5
117
0
5
Order By: Relevance
“…The induction of the defense responses described is not linked to strong PR-1 gene expression. This is consistent with the observation that the coordinately regulated maize PR-1 and PR-5 genes are more rapidly and strongly induced in incompatible than in compatible interactions with the rust fungus Puccinia sorghi (Morris et al, 1998). The finding that U. maydis Dmrb1 mutants triggered pronounced PR-1 expression despite low fungal colonization relative to wild-type infection leads to the assumption that U. maydis escapes induction of a classical host defense due to its proliferation capacity.…”
Section: Umi Genes Related To Secondary Metabolism and Defensesupporting
confidence: 89%
See 1 more Smart Citation
“…The induction of the defense responses described is not linked to strong PR-1 gene expression. This is consistent with the observation that the coordinately regulated maize PR-1 and PR-5 genes are more rapidly and strongly induced in incompatible than in compatible interactions with the rust fungus Puccinia sorghi (Morris et al, 1998). The finding that U. maydis Dmrb1 mutants triggered pronounced PR-1 expression despite low fungal colonization relative to wild-type infection leads to the assumption that U. maydis escapes induction of a classical host defense due to its proliferation capacity.…”
Section: Umi Genes Related To Secondary Metabolism and Defensesupporting
confidence: 89%
“…This gene is strongly expressed during a resistance response in incompatible interactions, while in successful infections expression is weak and attenuated (Morris et al, 1998). PR-1 gene expression was examined in the tissue probes T1 to T10 (Fig.…”
Section: Comparison Of Umi2 With Pr-1 Gene Expressionmentioning
confidence: 99%
“…In maize, the induction of four genes, PR1, PR5, PRms, and Wip1, has been associated with the HR defense response (Casacuberta et al 1992;Rohrmeier and Lehle 1993;Morris et al 1998;Simmons et al 2002). We examined their expression in relation to developing Rp1-D21 lesions by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Figures 2 and 3 show that the Rp1-D21 phenotype is associated with the production of superoxide and H 2 O 2 , together with the induction of the genes PR1, PR5, PRms, and WIP1, all hallmarks of a bona fide HR. It should be noted that these genes can also be induced by a defense response not including HR and by various other stresses including wounding (Casacuberta et al 1991(Casacuberta et al , 1992Rohrmeier and Lehle 1993;Morris et al 1998;Dunkle and Levy 2000). Even so, the preponderance of evidence suggests that Rp1-D21 triggers an exaggerated form of the normal maize hypersensitive response.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lozovaya et al (1998) reported that the presence of A. flavus caused an increase in b-1,3-glucanase activity in callus tissues of a resistant genotype, but not in a susceptible one. A more rapid and stronger induction of the pathogenesis-related (pr1 and pr5) genes in maize leaves has also been observed in a resistant reaction when compared to a susceptible reaction upon pathogen infection (Morris et al, 1998). In another investigation, a 14 kDa trypsin inhibitor (TI) protein was found constitutively produced at high levels in resistant lines but at low levels or was missing in susceptible ones (Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 89%